Pengaruh Pandemi Terhadap Perilaku Konsumen Dalam E-commerce - Selfiana Dewi; Rayyan Firdaus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The coronavirus is the cause of the COVID-19 pandemic. The government is implementing policies that limit community activities to reduce the number of positive cases. The community experiences many effects, especially the lack of access to buy daily necessities. As a result, many people switch to online shopping rather than shopping directly in shops, markets, supermarkets, and so on, one of which is e-commerce. It is hoped that this article will be able to find out how the corona pandemic affects e-commerce and consumer behavior. The results show that the corona pandemic can have a positive impact on e-commerce, consumer behavior and e-commerce.